Global antimony supply risk assessment through the industry chain - Li, Junhui; Xu, Deyi; Zhu, Yongguang (Frontiers in Energy Research, 2022)
Antimony is a type of critical metal for the energy transition. The antimony industry chain is distributed among the major developed and developing countries around the world. With the development of clean energy technology, the demand for antimony in photovoltaic and energy storage fields will increase significantly. Considering the significant changes in the global demand for antimony products and the serious supply shortage, people should pay more attention to the supply risk of related products of the antimony industry chain. In this paper, we propose a new integrated index to evaluate the supply risk of antimony industry chain related products, including Herfindahl Hirschman index, global governance index, human development index, global innovation index, and betweenness centrality in complex networks. Meanwhile, seven commodities in the antimony industry chain are selected for empirical analysis from 2011 to 2019. The results show that countries with high supply risks of the industry chain upstream include Canada, France, Germany, India, Japan, Thailand, and the United Kingdom. And, Australia, India, Japan, Thailand, and Vietnam are with high supply risks in the midstream of the industry chain. Meanwhile, Canada, India, Japan, and Thailand are with high downstream supply risks. Some countries, like China, the United States, and Germany, play a core role in different sectors of the industry chain. International competitive relations of countries have caused a high supply risk of products related to the antimony industry chain. The supply risk of the antimony industry chain shows that countries must strengthen industrial division and cooperation to maximize their interests. It is suggested to take the country-specific measures to mitigate supply risks, including establishing national inventories of critical materials, overseas investment, strengthening the guidance of industrial policies, and accelerating infrastructure construction.